DEVELOPMENT OF THE ASOKA TRAINING MODEL BASED ON SOCIAL LITERACY IN HIGHER EDUCATION - Abdul Rahmat; Eri Sarimanah; Mira Mirnawati; Ahmad (European Journal of Humanities and Educational Advancements, 2023)
ASOKA training aims For form participant training to have high competence and capability convey his idea to public on base experience learning in the environment social , refers to five stages ie stages experience, convey, process, criticize and act. Study development of training models This conducted at Gorontalo State University with use approach study mix. Election method mixture caused For producing the ASOKA training model involves as many as 150 good people as subject research , respondents model testing , content validator , empirical validator, and model reviewer. Research data obtained with spread questionnaire and analysis document. Research samples involved in model testing is semester 3-6 students are taken purposive sampling. Research data consists from quantitative data processed with use analysis inferential with use Jeffery Amazing Statistics Program formulation while qualitative data processed with Robert K. Yin’s approach.